Dynamic characteristics of multi-charged ions emitted from nanosecond laser produced molybdenum plasmas. Issue 4 (26th February 2020) - Wu, Ding; Mao, Xianglei; Chan, George C.-Y.; Russo, Richard E.; Zorba, Vassilia; Ding, Hongbin
Abstract : The charge state distribution and temporal evolution of laser-produced molybdenum plasma were investigated at various laser power densities. Abstract : Diagnostics of plasma–wall interaction processes provide important information on nuclear fusion devices. Elucidation of the charge state distribution and temporal evolution of multi-charged ions is essential to improve laser ablation-based diagnostics of the plasma–wall interaction processes. Molybdenum is a material of interest in fusion and has been used as the plasma-facing material of the first wall in the EAST tokamak. In this work, the dynamic characteristics of multi-charged ions emitted from a molybdenum plasma produced by a Q-switched Nd:YAG nanosecond laser (wavelength 1064 nm, pulse width 7 ns) were studied using time of flight mass spectroscopy under a pressure of 6 × 10 −4 Pa. The charge state distribution and temporal evolution of the multi-charged ions at various laser power densities from 0.85 GW cm −2 to 7.9 GW cm −2 were systematically investigated. This power density range is commensurate with that used in LIBS and LIAS diagnostics of the plasma–wall interaction process in EAST tokamaks. The ion charge state was found to increase with laser power density and the observed maximum charge state was up to seven at the highest laser power density used in these experiments. The higher charged ions had greater velocities indicating that separation took place between the different charged ions during the plasma expansion process. The origin of multi-charged ions is attributed to step-wise ionization due to plasma shielding from strong laser absorption in the plasma and the reduction of the ablation rate with the increase in laser power density. The velocities between these multi-charged ions were related to the acceleration of the transient plasma sheath during the laser interaction with the target and plasma.